Ocular administration of acetazolamide microsponges in situ gel formulations - Manar M. Obiedallah; A.M. Abdel-Mageed; Tahani H. Elfaham (Elsevier, 2018)
In the present work, the antiglaucoma drug, acetazolamide, was formulated as microsponges in situ gel for ocular drug delivery aiming an improved therapeutic efficacy and reduction in the systemic side effects of oral acetazolamide. The microsponges were prepared by the quasi emulsion solvent diffusion method and were incorporated into 25% pluronic F-127 in situ gel. Ethyl cellulose polymer in different proportions with drug was used to prepare the microsponges. Different parameters were evaluated to select the best formulation. The formula S2 with drug to polymer ratio (2:1) showed high entrapment efficiency of about 82% and mean particle size of about 10 µm with polydispersity index (PDI) of 0.22, which are suitable characters for ocular delivery. The in situ gels were evaluated for physicochemical properties (pH, gelling capacity, gelation time and rheological properties) and in vivo studies. S2 formulation showed higher therapeutic efficacy compared to free drug in gel. It was non irritant to the rabbit's eye. These results indicated that acetazolamide microsponges in situ gel have potential ability for ophthalmic delivery. Keywords: Microsponges, Acetazolamide, Ophthalmic gels, Intraocular pressure